Investigating traffic accidents: A collision of two motor vehicles - Prentkovskis, Olegas; Sokolovskij, Edgar; Bartulis, Vilius (Transport, 2010)
Traffic safety may be ensured by normal operation of all elements of the system, including the driver, a motor vehicle and transportation medium. Insufficient safety of some particular elements of this system (the lack of discipline of the participants of traffic, poor technical state of a motor vehicle or road, etc.) are the main causes of traffic accidents. Statistical data on traffic accidents in 2000–2009 in Lithuania is presented. Collisions of motor vehicles in 2009 make one of the largest proportion of all traffic accidents ‐ 33.4%. In 2009 drivers, were the main traffic accident perpetrators ‐ 73.6%. The paper considers some major aspects of motor vehicle collision simulation based on the application of PC‐CRASH software, allowing researchers to analyze the changes in the direction of motor vehicle motion in the case of a collision and the influencing factors. This type of traffic accident simulation consists in studying the circumstances of collision, reconstructing the processes, calculating the pre‐impact speed of motor vehicles and deter‐ mining various parameters of motor vehicles’ movement at different stages of traffic accident development.First published online: 24 Jun 2011